Cigarette smoking, gastric acid secretion, and serum pepsinogen I concentrations in duodenal ulcer patients. Issue 12 (December 1985) - Parente, F; Lazzaroni, M; Sangaletti, O; Baroni, S; Bianchi Porro, G
Abstract : Cigarette smoking has been linked with duodenal ulcer disease although the mechanism of this association is unclear. This study assessed basal gastric secretory response to acute smoking of smokers with an active duodenal ulcer; in addition the possible effects of chronic smoking on gastric secretory capacity, as expressed by pentagastrin stimulated gastric acid secretion and fasting serum pepsinogen I (PG I) concentrations, were investigated in patients with active duodenal ulcer, or non-ulcer dyspepsia. In 10 smokers with duodenal ulcer smoking four cigarettes during 40 minutes did not influence basal gastric secretion of acid and pepsin, or serum PG I and gastrin concentrations. In 136 patients with duodenal ulcer and 90 controls with non-ulcer dyspepsia, pentagastrin stimulated acid secretion and fasting serum PG I concentrations were significantly higher among habitual heavy smokers than among non-smokers. These findings suggest that in heavy smokers with duodenal ulcer acid- and pepsin-secreting cell function is not affected by acute cigarette smoking. By contrast, chronic cigarette smoking seems to be associated either with an increase of parietal- and chief-cell mass, or with an enhancement of their secretory capacity.